Yb3+, Tm3+ and Ho3+ triply-doped tellurite core-cladding optical fiber for white light generation - Manzani, D. [UNESP]; Ledemi, Y. [UNESP]; Skripachev, I. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; de Oliveira, R. E. P.; de Matos, C. J. S. (Optical Soc Amer, 2011)
Tellurite glass is proposed as a host for Yb3+, Tm3+ and Ho3+ triply doped optical fiber and, in this work, a new multimode optical fiber with triply-doped core was fabricated. We report results on the processing and characterization of tellurite-based glass preforms and fibers. Cr3+ was used as tracer to assess core quality and uniformity across 60 mm length preform. By Raman fluorescence of Tm3+ ions contained into the core, we also mapped the interface between core and cladding that reveals an interface around 45 mu m for a 10.11 mm of preform. For triply-doped core fiber excited at 980 nm, we generated white light radiation. The chromaticity diagram showed the multicolor emission and the color tunability of the triply-doped core optical fiber. (C) 2011 Optical Society of America